Love in arabic novels: cultural narratives and literary expressions - Zulkepli, Muhamad Khairul Anuar (Universiti Teknologi MARA, Kedah, 2025)
Love has manifested itself in numerous ways in Arabic literature for centuries and continues to be one of the most loved themes. Most of the love in the arabic literary desert travels unexplored with more than rather romance. Most importantly, the recent works of Arabic literature have included the third dimensional love espoused in the female gaze. This is especially the case in modern Arabian, where the rereading of the traditional notions of love has taken place through the relaying of nation building, modernity and cultural identity concepts (Oghia, 2015). Such novels usually oscillate between the utopic view of love as presented in the classical Arabic love poems and the reality of the current Arab world (Radwan, 2023). Through these love stories, the authors address the concerns of the age regarding the relationship between tradition and modernity. Literature therefore explores the ways personal feelings intertwine with the feelings of society at large. Love in Arabic novels is integrated with issues of politics and history, which makes such literature transform, instead of simply narrate, aspects of Arab culture (Ouyang, 2012). This paper will consider the manifestations of love within the framework of Arabic novels, focusing on love as a literary expression of culture that creates a bridge between private experience and public, rather national and cultural, feelings.